Farmers knowledge, perceptions and management of Kersting’s groundnut (Macrotyloma geocarpum Harms) insect pests in Benin - Loko, Y.L.E.; Akohonwe, J.; Toffa, J.; Orobiyi, A.; Assogba, Perceval; Dansi, A.; Tamò, Manuele (Springer, 2019)
Background Macrotyloma geocarpum Harms is a neglected and underutilized crop in Benin subject to several constraints including storage insect attacks, which contribute to the decrease in its production. An ethnobotanical survey using a semi-structured questionnaire was conducted in 15 villages in southern and central Benin to document farmers’ perceptions of M. geocarpum storage insect pests and their traditional management practices.